2019
DOI: 10.1128/msphere.00728-19
|View full text |Cite
|
Sign up to set email alerts
|

Rousette Bat Dendritic Cells Overcome Marburg Virus-Mediated Antiviral Responses by Upregulation of Interferon-Related Genes While Downregulating Proinflammatory Disease Mediators

Abstract: Dysregulated and maladaptive immune responses are at the forefront of human diseases caused by infection with zoonotic viral hemorrhagic fever viruses. Elucidating mechanisms of how the natural animal reservoirs of these viruses coexist with these agents without overt disease, while permitting sufficient replication to allow for transmission and maintenance in a population, is important for understanding the viral ecology and spillover to humans. The Egyptian rousette bat (ERB) has been identified as a reservo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 47 publications
4
31
0
Order By: Relevance
“…To further validate that in vivo CD14 + splenocyte responses to MARV reflected direct infection of and replication in monocytes/macrophages, which are primary MARV targets in primates, we infected ex vivo CD14 + splenocytes from naive colony ERBs with a recombinant version of the same MARV bat isolate used for our ERB inoculations. 7,21,25,26,36,37 This rMARV encodes a ZsGreen (ZsG) fluorescent protein able to visualize successful filovirus replication. 36,37 As expected, CD14 + populations showed robust ex vivo infection, with ZsG fluorescence increasing across the cell monolayer in both breadth and intensity out to D3 ( Figure S1B).…”
Section: Cd14 + Splenocytes From Marv-infected Erbs Are Efficiently Amentioning
confidence: 99%
See 2 more Smart Citations
“…To further validate that in vivo CD14 + splenocyte responses to MARV reflected direct infection of and replication in monocytes/macrophages, which are primary MARV targets in primates, we infected ex vivo CD14 + splenocytes from naive colony ERBs with a recombinant version of the same MARV bat isolate used for our ERB inoculations. 7,21,25,26,36,37 This rMARV encodes a ZsGreen (ZsG) fluorescent protein able to visualize successful filovirus replication. 36,37 As expected, CD14 + populations showed robust ex vivo infection, with ZsG fluorescence increasing across the cell monolayer in both breadth and intensity out to D3 ( Figure S1B).…”
Section: Cd14 + Splenocytes From Marv-infected Erbs Are Efficiently Amentioning
confidence: 99%
“…Thus, these two species-specific antibodies efficiently and selectively target and magnetically isolate ERB cells characteristic of monocytes/macrophages and B cells, agreeing with their cytometric analysis in our previously published BMDC ex vivo study, and ERB CD14 + monocytic cells are a direct cellular target of MARV infection, reflecting the established MARV tropism of their primate counterparts. 7,21,25 MARV-Infected ERBs Become Temporarily Viremic with Virus Dissemination to Tissues MARV RNA levels in blood were first detected on D1, peaked at D5, and were undetectable by D14 ( Figure 2A). Consistent with previous studies, similar viral RNA (vRNA) kinetics were observed in skin at the inoculation site ( Figure 2B) and in whole liver and spleen ( Figure 2C), persisting in the spleen for longer (D14) than in liver or skin (D8).…”
Section: Cd14 + Splenocytes From Marv-infected Erbs Are Efficiently Amentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro and laboratory studies demonstrate that bats can specifically regulate naïve immunity pathways to effectively cope with viral infection [114]. For example, dendritic cells generated from the bone marrow of the Egyptian rousette (Rousettus aegyptiacus) infected with Marburg virus down-regulate immune-stimulatory pathways and maturation of cells targeted by the virus while up-regulating pathogen-sensing pathways [115]. Unique bat immune regulation may occur with MERS-CoV infection, at least under experimental conditions [101].…”
Section: Proactively Connecting the Wellbeing Of Human And Bat Populamentioning
confidence: 99%
“…Even if MARV infection of these cell lines does not lead to IFN-ω induction, it is still possible that various primary cell types could serve as a source of IFN-ω in vivo. It has recently been shown that Egyptian rousette dendritic cells that are infected with a bat isolate of MARV upregulate IFNs and ISGs, though the few IFNω genes included in the Nanostring-based study were not reported to be significantly upregulated (63).…”
Section: Discussionmentioning
confidence: 94%